Effects of ENSO on cold - air activities and tropical cyclones in Vietnam - Duc Ngu Nguyen (Vietnam Journal of Science, Technology and Engineering, 2017)
This paper presents a summary of the results of a study into the effects of ENSO (El Niño and La Niña) on the frequency of cold fronts and tropical cyclones affecting Vietnam. The results show that, during the ENSO periods, cold air activities affecting Vietnam were reduced. The ratio of total positive anomalies to negative anomalies of front frequency was 68% in the case of El Niño, and 60% in the case of La Niña. The frequency of tropical cyclones affecting Vietnam decreased by 28% in the case of El Niño, and increased to 38% in comparison with the multiyear average in the case of La Niña. During the El Niño period, hurricanes affecting Vietnam were often evenly distributed or concentrated in the first half of the typhoon season, but during the La Niña period, hurricanes were concentrated in the second half of the hurricane season.